A scoping review of different monitoring-technology devices in caring for older adults with cognitive impairment - Asiri, Hind Mohammed; Asiri, Asia Mohammed; Alruwaili, Hana Falah; Almazan, Joseph (Frontiers in Public Health, 2023)
Various monitoring technologies developed in preventing potential complication problems among older adults with cognitive impairment and towards their cognitive function improvement. This scoping review identifies gaps in monitoring technology devices for cognitive health status and highlights areas that require further inquiry. The study used the Joanna Briggs Institute (JBI) and the PRISMA extension for scoping reviews checklist using the eligibility criteria Population, Concept, Context (PCC) framework. The population is older adults, 65 years old or older while the concept and context are monitoring technology devices utilized in detecting and caring for an older adult with cognitive impairment. There are three electronic databases (Medline, Scopus, and Web of Science) were included and a total of 21 articles met the selection criteria. Several monitoring innovative technology-based program devices for screening assessing, detecting, and monitoring interventions for older adult cognitive impairment and together with family caregivers for the continuity of care were established. Monitoring devices are useful in older adult safety, improve the quality of life by enabling them to live independently for longer, and improved mental well-being to help reduce the burden on caregivers by providing them with information about the older adult's activity. Moreover, studies have shown that with proper education and training, older adults and their caregivers can learn to use these devices effectively and comfortably. These results provide crucial insights into innovative technology that assessed cognitive health, which could have a substantial effect in improving their mental health and using this baseline information in supporting public health policy in enhancing their quality lives.